2008
DOI: 10.1158/1055-9965.epi-07-2717
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 8-Oxo-7,8-Dihydro-2′-Deoxyguanosine in Patients with Parasite Infection and Effect of Antiparasitic Drug in Relation to Cholangiocarcinogenesis

Abstract: Parasite infection of Opisthorchis viverrini is a major risk factor for cholangiocarcinoma. Our previous immunohistochemical studies showed that O. viverrini infection induced oxidative DNA lesions in the bile duct epithelium during cholangiocarcinoma development. The current study assessed the levels of 8-oxo-7,8-dihydro-2 ¶-deoxyguanosine (8-oxodG), an oxidative DNA lesion, in the urine and leukocytes of O. viverrini -infected subjects and cholangiocarcinoma patients. Forty-nine O. viverrini -infected patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 33 publications
4
56
0
Order By: Relevance
“…Upregulation of inducible nitric oxide synthase (iNOS) and subsequent oxidative/nitritative DNA damage has been demonstrated in Opisthorchis viverrini-related cholangiocarcinoma in humans (54) , and in Clonorchis sinensis infected mice (49,55) . Oxidative/nitritative damage to proteins via reactive oxygen species may prolong the oxidative stress (37) .…”
Section: Cholangiocarcinomamentioning
confidence: 99%
“…Upregulation of inducible nitric oxide synthase (iNOS) and subsequent oxidative/nitritative DNA damage has been demonstrated in Opisthorchis viverrini-related cholangiocarcinoma in humans (54) , and in Clonorchis sinensis infected mice (49,55) . Oxidative/nitritative damage to proteins via reactive oxygen species may prolong the oxidative stress (37) .…”
Section: Cholangiocarcinomamentioning
confidence: 99%
“…Diverse exposure to risk factors for CCA result in varying geographic incidences with parasitic infections, such as liver fluke, Opisthorchis viverrini (O. viverrini), chronic viral hepatitis and cirrhosis including hepatitis C virus (HCV), hepatitis B virus (HBV), liver cirrhosis, and hepatolithiasis (Shin et al, 2010). A major mechanism linking between inflammation and CCA is related to the generation of free radicals such as superoxide anion (O2¯•), nitric oxide (NO) and other reactive oxygen (ROS) * and nitrogen species (RNS) which cause DNA damage and the alteration of gene expressions in both a hamster animal model and humans (Jaiswal et al, 2000;Pinlaor et al, 2003;Thanan et al, 2008;Yongvanit et al, 2012b). Regarding to the molecular mechanism underlining CCA progression, there are some studies have demonstrated aberrant expression of potential genes involving in CCA (Kunlabut et al, 2012;Namwat et al, 2012;Thongchot et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(7,8) Recently, Pinlaor et al (9) suggested that oxidative and nitrosative damage to DNA in the liver of Ov-infected hamsters can play a key role in the modulation of gene expression, which enhances the effect of the DNA adduct and can drive a normal cell undergo tumor development. Additionally, Thanan et al (10) reported that the highest 8-oxodG level, which is the biomarker of DNA damage, was observed for CCA patients, and a higher level was found in the urine and leukocytes of Ov-infected patients than that in healthy patients.The gene expression profiles of Ov-associated CCA tumors, as investigated by Loilome et al(11) , indicated that myristoylated alanine-rich protein kinase C substrate (MARCKS) is significantly upregulated in tumor tissues, suggesting a role for this protein in cholangiocarcinogenesis. MARCKS is a ubiquitous heat-stable protein (12)(13)(14) that shuttles between the plasma membrane and cytoplasm in a protein kinase C (PKC) phosphorylation-dependent manner.…”
mentioning
confidence: 99%
“…(7,8) Recently, Pinlaor et al (9) suggested that oxidative and nitrosative damage to DNA in the liver of Ov-infected hamsters can play a key role in the modulation of gene expression, which enhances the effect of the DNA adduct and can drive a normal cell undergo tumor development. Additionally, Thanan et al (10) reported that the highest 8-oxodG level, which is the biomarker of DNA damage, was observed for CCA patients, and a higher level was found in the urine and leukocytes of Ov-infected patients than that in healthy patients.…”
mentioning
confidence: 99%